2014
DOI: 10.1039/c4ra04197f
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of carbon nanotubes by chitosan in a nanohybrid conductive polymer composite for detection of polar vapours

Abstract: A new hybrid nanocomposite was designed by introducing decorated CNTs into a polymer for improving the sensitivity against polar vapours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Previous studies have demonstrated that hybrid materials are highly suitable in sensing applications, showing enhanced sensor stability, sensitivity and selectivity. The inorganic phase can be diverse, ranging from metal oxides, metal nanoparticles, carbon nanotubes and graphene . Their incorporation into conducting polymers can increase the concentration of interacting sites with the analytes, improve the intra‐ and inter‐chain mobility of charge carriers in the polymer chains or even modify the affinity of the composite to the electron‐donor or ‐acceptor molecules .…”
Section: Materials For Gas Sensing21single‐element Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that hybrid materials are highly suitable in sensing applications, showing enhanced sensor stability, sensitivity and selectivity. The inorganic phase can be diverse, ranging from metal oxides, metal nanoparticles, carbon nanotubes and graphene . Their incorporation into conducting polymers can increase the concentration of interacting sites with the analytes, improve the intra‐ and inter‐chain mobility of charge carriers in the polymer chains or even modify the affinity of the composite to the electron‐donor or ‐acceptor molecules .…”
Section: Materials For Gas Sensing21single‐element Materialsmentioning
confidence: 99%
“…In addition to metal oxides and metals, carbon nanostructures such as CNTs and graphene are also promising additives for conducting polymers to develop room‐temperature gas‐sensing materials. For example, Swager et al have shown that the CNTs/polythiophene hybrids are highly sensitive and selective to organic vapors.…”
Section: Materials For Gas Sensing21single‐element Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct comparison of response values cannot be fair for the performance evaluation since the reported studies applied different test procedures and defined response parameters with different methodologies. For example, in two of the studies, response values were fitted by using the Langmuir-Henry-Clustering (LHC) model to correlate gas sensing with properties of CNT-chitosan and polyvinly alcohol (PVA)-chitosan-CNT blended films [12,18]. Thus, they used nitrogen as a carrier gas during their measurements.…”
Section: Uv Effect On Sensingmentioning
confidence: 99%
“…In addition to these, chitosan was used in more complex composites for gas sensing [16,17]. Molla-Abbasi and Ghaffarian suggested the use of chitosan-decorated carbon nanotube surfaces for polar chemical vapors [18]. They discovered improved humidity sensing abilities of chitosan@CNT heterostructures related with the chitosan surfaces.…”
Section: Introductionmentioning
confidence: 99%